BEAT MOTORCYCLE CONECTING ROD MOLD DESIGN USING MASTER CAM X5 AND INVENTOR - intipada, dava; Santosa, Aa (Universitas Majalengka, 2024)
In its development, every manufacturing industry increasingly makes people think more creatively and are faced with new problems, especially in making new innovations. The aim of these production problems is to achieve production targets more quickly and efficiently. The metal machining process is an important factor to support the final quality of the product, but there is one obstacle that must be faced, how to determine the appropriate manufacturing process to make a product with better accuracy. The increasing development of technology in the casting manufacturing sector due to consumer demands for better quality encourages the industry to innovate, the process of making automotive components, especially connecting rods, currently uses metal molds with the aim of improving the quality of these components. The connecting rod functions to connect the piston to the shaft. This component can be a bridge for combustion power and can be channeled directly to the crankshaft. Please note that a car engine can go fast because the piston hits the crankshaft and the connecting rod which is the connecting rod. Without a connecting rod, the car will not be able to accelerate optimally A design process has been carried out to make a connecting rod mold using Master Cam X5, to produce Code G which will be used to make a mold on a CNC machine. The material used is Alamunium 2024.